E-Type Asteroid (2867) Steins as Imaged by OSIRIS on Board Rosetta - Keller, H. U.; Barbieri, C.; Koschny, D.; Lamy, Philippe; Rickman, H.; Rodrigo, R.; Sierks, H.; A'Hearn, Michael F.; Angrilli, F.; Barucci, M. A.; Bertaux, Jean-Loup; Cremonese, Gabriele; et al. (Science, 2010)
International audience The European Space Agency's Rosetta mission encountered the main-belt asteroid (2867) Steins while on its way to rendezvous with comet 67P/Churyumov-Gerasimenko. Images taken with the OSIRIS (optical, spectroscopic, and infrared remote imaging system) cameras on board Rosetta show that Steins is an oblate body with an effective spherical diameter of 5.3 kilometers. Its surface does not show color variations. The morphology of Steins is dominated by linear faults and a large 2.1-kilometer-diameter crater near its south pole. Crater counts reveal a distinct lack of small craters. Steins is not solid rock but a rubble pile and has a conical appearance that is probably the result of reshaping due to Yarkovsky-O'Keefe-Radzievskii-Paddack (YORP) spin-up. The OSIRIS images constitute direct evidence for the YORP effect on a main-belt asteroid.